Introduction to industrial polypropylene : properties, catalysts, processes - Malpass, Dennis B.; Band, Elliot I.; Wiley InterScience (Online service) (Hoboken, N.J. : John Wiley & Sons ; Salem, Mass. : Co-published with Scrivener Pub., 2012)
"This introductory text is an important resource for new engineers, chemists, students, and chemical industry personnel to understand the technical aspects of polypropylene which is the 2nd largest synthetics polymer in manufactured output."--Provided by publisher.
6.6 Characteristics of mPP.
Includes bibliographical references and index.
Print version record.
Keywords: Polypropylene; Polymers; Polymerization; Engineering; Chemical engineering; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Polymerization; Polymers; Polypropylene; Electronic books